Clinical evaluation of commercial automated SARS-CoV-2 immunoassays - Kittel, Maximilian; Thiaucourt, Margot; Gerhards, Catharina; Haselmann, Verena; Neumaier, Michael (International journal of infectious diseases, 2021)
Objective - Numerous immunoassays for detecting antibodies directed against SARS-CoV-2 have been rapidly developed and released. Validations of these have been performed with a limited number of samples. The lack of standardisation might lead to significantly different results. This study compared ten automated assays from six vendors in terms of sensitivity, specificity and reproducibility. - Methods - This study compared ten fully automated immunoassays from the following vendors: Diasorin, Epitope Diagnostics, Euroimmun, Roche, YHLO, and Snibe. The retrospective part of the study included patients with a laboratory-confirmed COVID-19 infection, and controls comprised patients with a suspected infection, in whom the disease was excluded. Furthermore, biobanked sera were taken as negative controls (n = 97). The retrospective part involved four groups: (1) laboratory-confirmed COVID-19 infection (n = 183); (1B) suspected COVID-19 infection (n = 167) without a qRT-PCR result but positive serological results from at least two different assays, and suspected COVID-19 infection due to a positive serological result from the Roche assay (n = 295); (2) biobanked sera obtained from patients before the emergence of SARS-CoV-2 (n = 97) as negative controls; and (2A) probably COVID-19-negative sera with negative serological results from at least two different assays (n = 152). - Results - Overall diagnostic sensitivities were: Euroimmun (IgA) 87%; Epitope Diagnostics (IgG) 83%; YHLO (IgG) 77%; Roche (IgM/IgG) 77%; Euroimmun (IgG) 75%; Diasorin (IgG) 53%; Epitope Diagnostics (IgM) 52%; Snibe (IgG) 47%; YHLO (IgM) 35%; and Snibe (IgM) 26%. Diagnostic specificities were: YHLO (IgG) 100%; Roche, 100%; Snibe (IgM/IgG) 100%; Diasorin (IgG) 97%; Euroimmun (IgG) 94%; YHLO (IgM) 94%; Euroimmun (IgA) 83%. - Conclusion - Assays from different vendors substantially varied in terms of their performance. These findings might facilitate selection of appropriate serological assays.
Gesehen am 31.03.2021